Literature in Education Frame: Poetry as a Bridge to Introduce Literature for Junior High School Students - Lilik Purwaningsih; Sopian Sopian; Nurdani Yulian Ahmad (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the use of approaches, methods, and strategies in teaching poetry appreciation in junior high schools, to identify the materials used, and to analyze the forms of evaluation applied in the learning process. This type of research is qualitative descriptive, where observation and interviews are used to collect data. Descriptive analysis is used to analyze the findings. The results show that various strategies are used in teaching poetry. Project-Based Learning 21%, Inquiry 24%. Problem-Based Learning 13%, Demonstration 34%, Collaborative 16%, Cooperative 26%, Synectics 32%. The materials used are books 42%, Authentic Materials 15%, handouts 33%, poetry texts 10%. Evaluation in teaching poetry in literature appreciation subjects uses standard evaluations/assessments by conducting three indicators, namely reading, creating, and analyzing. The implications of this research can provide new ideas in the field of instructional design on how to enhance critical thinking and critical awareness in Indonesian students through practical analysis of reading poetry and how poetry can motivate students and help them grow as individuals.